1981
DOI: 10.1172/jci110141
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of hepatic triglyceride synthesis in diabetic rats.

Abstract: A B S T R A C T The syntheses of triglyceride and its precursors were increased when liver homogenates of ketotic diabetic rats were incubated with [U-14C]-glycero 3-phosphate and cofactors. Triolein sonicates produced a concentration-dependent inhibition of the synthesis of both diglyceride and triglyceride, whereas monoolein sonicates had no effect. Rat In studies on the site of inhibition oftriglyceride synthesis in the overall biosynthetic pathway, serum very low density lipoproteins produced a concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Cholesterol metabolism also changed over time in both groups. Murthy and Shipp (1981) reported that cholesterol concentration was non-significantly higher during estrus. Cholesterol is a key component of steroid hormones.…”
Section: Resultsmentioning
confidence: 98%
“…Cholesterol metabolism also changed over time in both groups. Murthy and Shipp (1981) reported that cholesterol concentration was non-significantly higher during estrus. Cholesterol is a key component of steroid hormones.…”
Section: Resultsmentioning
confidence: 98%
“…These studies support a role for enhanced triacylglycerol synthesis in the pathogenesis of alcoholic steatosis. However, in animal studies the data suggests that as lipid accumulation progresses, hepatic triacylglycerol synthesis becomes depressed, possibly due to the inhibitory effect of very low density lipoprotein triacylglycerol on PAH activity (Murthy & Shipp, 1981). Recent evidence suggests that before incorporation into very low density lipoproteins cytosolic triacylglycerol must undergo lipolysis and subsequent re-esterification (Gibbons et al, 1994;Yang et al, 1995), impairment of this process may also contribute to hepatic lipid accumulation.…”
Section: Hepatic Glycerolipid Synthesismentioning
confidence: 99%